2008
DOI: 10.1007/s00436-008-1076-3
|View full text |Cite
|
Sign up to set email alerts
|

A case report: Entamoeba histolytica infections in the rhesus macaque, China

Abstract: A case of amebic dysentery due to a natural infection of Entamoeba histolytica in the rhesus macaque (Macaca mullata) was reported. A fecal specimen was isolated and identified by the polymerase chain reaction technique. A daily dose of 750 mg of metronidazole was given orally for 10 days, and good results were observed. The early diagnosis of an E. histolytica infection allowed a proper antiamoebic treatment in an early stage of infection resulting in a successful outcome after therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…in the current study was 66.7% which was lower than the findings from China (89.96%) (Zhang et al, 2019) and higher than those reported from Nepal (13.97% -32%) (Jha et al, 2011;Pokhrel and Maharjan 2014;Adhikari and Dhakal 2018;Bhattarai et al, 2019) and from India (10% -23.07%) (Parmar et al, 2012;Jaiswal et al, 2014). Several species of these pseudopodial amoebas like Entamoeba histolytica, E nuttalli, E. dispar, E. moshkovskii, E. hartmanni, E. chattoni, and E. polecki (Tachibana et al, 2007;Jiang et al, 2008;Tachibana et al, 2013;Guan et al, 2016;Zhang et al, 2019) have already been reported from macaques all over the world; however, majority of them are considered harmless and do not exhibit pathologic illness in the macaques. Pathologically, E. histolytica and E. nuttali are critical because they induce fatal intestinal and extraintestinal amebiasis (Fremming et al 1955;Loomis et al, 1983;Haq et al, 1985;Beaver et al, 1988;Pang et al, 1993;Verweij et al, 2003;Tachibana et al, 2007;Jiang et al, 2008;Levecke et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in the current study was 66.7% which was lower than the findings from China (89.96%) (Zhang et al, 2019) and higher than those reported from Nepal (13.97% -32%) (Jha et al, 2011;Pokhrel and Maharjan 2014;Adhikari and Dhakal 2018;Bhattarai et al, 2019) and from India (10% -23.07%) (Parmar et al, 2012;Jaiswal et al, 2014). Several species of these pseudopodial amoebas like Entamoeba histolytica, E nuttalli, E. dispar, E. moshkovskii, E. hartmanni, E. chattoni, and E. polecki (Tachibana et al, 2007;Jiang et al, 2008;Tachibana et al, 2013;Guan et al, 2016;Zhang et al, 2019) have already been reported from macaques all over the world; however, majority of them are considered harmless and do not exhibit pathologic illness in the macaques. Pathologically, E. histolytica and E. nuttali are critical because they induce fatal intestinal and extraintestinal amebiasis (Fremming et al 1955;Loomis et al, 1983;Haq et al, 1985;Beaver et al, 1988;Pang et al, 1993;Verweij et al, 2003;Tachibana et al, 2007;Jiang et al, 2008;Levecke et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Several species of these pseudopodial amoebas like Entamoeba histolytica, E nuttalli, E. dispar, E. moshkovskii, E. hartmanni, E. chattoni, and E. polecki (Tachibana et al, 2007;Jiang et al, 2008;Tachibana et al, 2013;Guan et al, 2016;Zhang et al, 2019) have already been reported from macaques all over the world; however, majority of them are considered harmless and do not exhibit pathologic illness in the macaques. Pathologically, E. histolytica and E. nuttali are critical because they induce fatal intestinal and extraintestinal amebiasis (Fremming et al 1955;Loomis et al, 1983;Haq et al, 1985;Beaver et al, 1988;Pang et al, 1993;Verweij et al, 2003;Tachibana et al, 2007;Jiang et al, 2008;Levecke et al, 2010). In our study, Entamoeba coli showed 57.1% prevalence rate which was higher than the previous findings from Nepal (9.52% -24.44%) (Jha et al, 2011;Bhattarai et al, 2019), India (10% -26.92%) (Parmar et al, 2012;Jaiswal et al, 2014), and China (42%) (Guan et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The focus on the interface between humans and wild macaques here is especially relevant in light of three factors. First, macaques are an established source of infectious zoonotic diseases and carriers of anthroponotic diseases, including cryptosporidiosis, giardiasis, and microsporidiosis [Edmonson et al, ; Ekanayake et al, ; Engel et al, ; Jiang et al, ; Jones‐Engel et al, ; McClure et al, ; Ye et al, ]. Second, previous work in this system has found intestinal helminthes, including hookworms, tapeworms ( Taenia spp.…”
Section: Introductionmentioning
confidence: 99%